Teleradiology in Southeast Iran: Evaluating the Views of Senior Executives and Radiologists. Issue 3 (July 2017) - Sadoughi, Farahnaz; Erfannia, Leila; Sancholi, Mahboobe; Salmani, Fatemeh; Sarsarshahi, Aida
Abstract : Teleradiology is considered as one of the important forms of telemedicine. Positive views of the users and providers of these services play an important role in its successful implementations. The aim of this study was to investigate the views of radiologists used in the radiology departments of teaching hospitals in the Zahedan University of Medical Sciences through teleradiology, as well as evaluate the executive possibility of teleradiology in these hospitals by the views of chief executive officer and comparison between these two views. The current cross-sectional research was performed in 2014 at Zahedan teaching hospitals. The views of 13 chief executive officers on the possibility of the execution of teleradiology and 26 radiologists on the teleradiology process were evaluated by means of two valid and reliable questionnaires. The results of the research revealed that most of the radiologists had knowledge of and positive opinions about teleradiology. Conversely, the view by chief executive officers was that implementation of these processes was not possible in the studied hospitals. Dealing with some issues including data security, controlling or restricting access to clinical information of patients during the process of teleradiology, the possibility of legal protection for the participating radiologists, constitution of executive teams in the organization along with the financial supports, and, subsequently, invitation of the supports from the chief executive officers as the main sponsors of teleradiology implementation in the teaching hospitals are all guidelines for improvement of the successful implementation of teleradiology.